2017
DOI: 10.1145/3057266
|View full text |Cite
|
Sign up to set email alerts
|

Fog Computing for Sustainable Smart Cities

Abstract: The Internet of Things (IoT) aims to connect billions of smart objects to the Internet, which can bring a promising future to smart cities. These objects are expected to generate large amounts of data and send the data to the cloud for further processing, specially for knowledge discovery, in order that appropriate actions can be taken. However, in reality sensing all possible data items captured by a smart object and then sending the complete captured data to the cloud is less useful. Further, such an approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
236
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(242 citation statements)
references
References 108 publications
(122 reference statements)
1
236
0
5
Order By: Relevance
“…Tang et al proposed a fog computing‐based big data analysis framework for smart cities. The proposed hierarchical framework provides responses in real time by applying analytics operations on the data generated from millions of devices deployed across the city . Gia et al introduced fog computing in the health‐care sector for real‐time monitoring of human health using IoT devices.…”
Section: Fog Computing Aspectsmentioning
confidence: 99%
“…Tang et al proposed a fog computing‐based big data analysis framework for smart cities. The proposed hierarchical framework provides responses in real time by applying analytics operations on the data generated from millions of devices deployed across the city . Gia et al introduced fog computing in the health‐care sector for real‐time monitoring of human health using IoT devices.…”
Section: Fog Computing Aspectsmentioning
confidence: 99%
“…On the contrary, our literature review revealed that Web-based applications achieve low energy consumption as a result of their on-demand and low-complexity features. The rationale behind this is that almost all of their heavy workloads are offloaded and performed remotely in the central server side [25,26]. In addition, the recent emergence of mobile edge/cloud computing technologies has provided effective cloudized computation infrastructure to promote the Web-based application approaches [27][28][29].…”
Section: Energy Consumption Problem Statementmentioning
confidence: 99%
“…The prevalent cloud models are not intended to handle the seven unprecedented V's (Volume, Velocity, Variety, Variability, Veracity, Visualization and Value) in the data generated by IoT architectures and coupling the whole universe of -things‖ or -objects‖ directly to the cloud is nearly unfeasible [10]. Fog computing approaches seem to be the preeminent preference for computations at the extreme edges such as vehicles, roadways, charging station etc [10]- [13]. However installation of fogs (mini data centers) everywhere across the edges of the networks and entities may not be cost productive.…”
Section: Fog Computing In Smart Grid-a Case Studymentioning
confidence: 99%